Serviço social e a intersetorialidade na saúde mental: uma revisão integrativa dos trabalhos publicados no CBAS - Araújo, Ana Katarina de (2019)
This paper aims to analyze the professional debate on intersectoriality in the field of mental health from the works published in the Brazilian Congress of Social Workers (CBAS). Thus, we sought to identify which understandings about intersectoriality, what the demands and how social workers trigger the strategy of intersectoriality in the field of mental health and what challenges pointed to the construction of intersectoral actions. With regard to methodological procedures, we adopted the narrative of bibliographical research, which was initially about the debate around the intersectoriality and later the relationship between the intersectoriality and the field of mental health, as well as the discussion about the linkage of Social Service with the intersectoriality in the field of mental health and systematic integrative research based on the studies of Botelho; Cunha and Macedo (2011) and Lima and Mioto (2007) for reading and analyzing the articles. For the selection of data, the bases of the Annals of the 10th to 15th CBAS were used in the period from 2001 to 2016, which marks the year of the Law of Psychiatric Reform and the last CBAS occurred, in which the Social Work completed 80 years of existence. The articles were selected based on the descriptors of "mental health", "intersectoriality", "mental health and intersectorality" and "intersectorality and health", selecting 148 articles, of which 37 were included for the construction of the syntheses. The research results showed that the understanding of Social Service in mental health on intersectoriality receives influences from the literature debate related to networking, interdisciplinarity and comprehensiveness, but has also tried to impress new meanings by relating intersectoriality to the confrontation of "social issues" and the reception of the users' demands. Social workers recognize the existing challenges, related mainly to objective issues, which relate to the constraints of the configuration of social policy itself in a context of neoliberalism, but have nevertheless assumed this attribution in the field of mental health to extend the realization of social rights of users. However, it is considered that faced with such difficulties the social worker or is unable to operationalize intersectoral actions or the way this articulation is materialized often does not express the professional capacity in articulating the theoretical-methodological, ethical-political and technical-operative dimensions, and can be approached in a timely and immediate manner.